Pengaruh Layanan Informasi Studi Lanjut Terhadap Minat Masuk Perguruan Tinggi Peserta Didik di Kelas XII SMA Negeri 8 Muaro Jambi - Susiana Susiana; Akmal Sutja; Rully Andi Yaksa (Departement of Mathematics Education, 2023)
Abstract Further studies are continuing schools of higher education a connection after graduating from a current higher education or school. Many factors cause students to decide not to continue their studies, namely external and internal factors. This study aims to reveal the effect of advanced study information services on students' interest in entering college in class XII at SMA Negeri 8 Muaro Jambi. The population in this study of class XII at SMA Negeri 8 Muaro Jambi. This sample was taken using a purposive sampling technique 30 students of class XII at SMA Negeri 8 Muaro Jambi This type of research is quantitative with a pre-experimental approach. The results of this study indicate that in general the interest in entering college of class XII students before being given treatment is at a moderate level with a percentage of 55.41%, which means that the interest of these students needs to be increased. And also in general the interest in entering college of class XII students after being given treatment is at a high level with a percentage of 72.59%, which means there is an increase in students' interest in going to college. The results also show that based on the results of hypothesis testing, it is known that the significance value is 0.000 <0.05 and the value of Tcount > Ttable or 6.128 > 2.042. It can be concluded that information services for advanced studies have an effect on increasing interest in entering college for class XII students at SMA Negeri 8 Muaro Jambi.